Development of Inclusive-Adaptive Disaster Mitigation Educational Media Based on Audio Visual and Sign Language to Improve Self-Rescue for Students with Disabilities - Serly Mahoklory (Jurnal Penelitian Pendidikan IPA, 2026)
Indonesia is a country with a high level of disaster vulnerability, yet mitigation education for students with disabilities, particularly those with hearing impairments, remains constrained by the limited availability of inclusive and adaptive learning media. This study aims to develop audio-visual disaster mitigation educational media combined with sign language to improve the self-rescue skills of students with disabilities. This study used a Research and Development (R&D) design, adapting the Borg and Gall model through the stages of needs analysis, design, development, expert validation, revision, and limited trials. The population consisted of 531 children with disabilities in Kupang City, from which a sample of 229 respondents was drawn using a purposive sampling technique. Data were collected through observation, interviews, questionnaires, and comprehension tests, and were analyzed using descriptive quantitative techniques (percentage and pre-test-post-test comparison) as well as qualitative analysis. The results of the study indicate that the developed media has a very high level of feasibility based on expert assessments and is able to significantly improve students' understanding and self-rescue skills. In addition, this media has been proven to increase student engagement and confidence in facing disaster situations. It is concluded that audio-visual and sign language-based educational media are effective, inclusive, and adaptive in supporting disaster mitigation learning for students with disabilities.